La corporeidad como estrategia para el desarrollo de habilidades y preservación de la salud en escolares en la nueva normalidad - Juárez Lozano, Ricardo (2020)
From the cultural historical activity theory, the development of the subjects is enhanced by teaching and in general by the systems of activity and communication in which they are inserted. Based on this, the project Motivando la Adecuada Recreación Activa y la Correcta Alimentación Saludable (Maracas, “Motivating Adequate Active Recreation and Correct Healthy Eating”), aims to be a program of physical activity and sport based on the development of life skills from a perspective of multiple intelligences. This article aims to inform the main results obtained in the psychological dimension of the project. To obtain the results, data were collected throughout the entire project and they were processed quantitatively in the Statistical Package for Social Sciences (SPSS), v. 25.0. The results point towards a differentiation in terms of gender when choosing to enter the program, as well as a strong influence of family culture in the decision to practice sports. The most developed skills in the participants were motor physics and they present a high development of their kinesthetic-bodily skills. The implications of such results are discussed as an alternative measure of promoting corporeity in the student during their vacation periods. Faced with the new normality, Physical Education at the basic education level becomes an indispensable subject for the preservation of health and the acquisition of healthy lifestyles. Keywords: Body, physical education, students, skill development.